Targeted exome sequencing profiles genetic alterations in leiomyosarcoma. Issue 2 (6th November 2015) - Agaram, Narasimhan P.; Zhang, Lei; LeLoarer, Francois; Silk, Tarik; Sung, Yun‐Shao; Scott, Sasinya N.; Kuk, Deborah; Qin, Li‐Xuan; Berger, Michael F.; Antonescu, Cristina R.; Singer, Samuel
Abstract : Leiomyosarcoma (LMS) belongs to the class of genetically complex sarcomas and shows numerous, often non‐recurrent chromosomal imbalances and aberrations. We investigated a group of LMS using NGS platform to identify recurrent genetic abnormalities and possible therapeutic targets. Targeted exome sequencing of 230 cancer‐associated genes was performed on 35 primary soft tissue and visceral (extra‐uterine) LMS. Sequence data were analyzed to identify single nucleotide variants, small insertions/deletions (indels), and copy number alterations. Key alterations were further investigated using FISH assay. The study group included patients with median age of 64 years and median tumor size of 7 cm. The primary sites included retroperitoneal/intra‐abdominal, extremity, truncal, and visceral. Thirty‐one tumors were high grade LMS, while four were low grade. Losses of chromosomal regions involving key tumor suppressor genes PTEN (10q), RB1 (13q), CDH1 (16q), and TP53 (17p) were the most frequent genetic events. Gains mainly involved chromosome regions 17p11.2 ( MYOCD ) and 15q25‐26 ( IGF1R ). The most frequent mutations were identified in the TP53 gene in 13 of 35 (37%) cases. FISH analysis showed amplification of the myocardin ( MYOCD ) gene in 5 of 25 (20%) cases analyzed. None of the four low grade LMS showed losses or mutations of PTEN or TP53 genes. Genetic complexity is the hallmark of LMS with losses of important tumor suppressor genes being a common feature. MYOCD, a key gene associated with smooth muscle differentiation, is amplified in a subset of both retroperitoneal and extremity LMS. Further studies are necessary to investigate the significance of gains/amplifications in the development of these tumors. © 2015 Wiley Periodicals, Inc.